MODERASI BERAGAMA DALAM ISLAM NUSANTARA: MENIMBA DARI WALI SONGO: LESSON LEARNT FROM NINE ISLAMIC SAINTS - Syamsurijal; Wasisto Raharjo Jati; Halimah Sa'diah (Jurnal Masyarakat dan Budaya, 2022)
“Islam Nusantara” (Islam of the Archipelago) is an idea and religious practice that represents reflection of Islam as non-violent, pro tolerance, equality, and accommodating to local cultures. These characters basically are principle of religious moderation. It is worth to note that the idea of “Islam Nusantara” has explained empirical and real Islamic values within religious moderation itself. For instance, “tawazun” (equality), “tawasuth” (moderation), and “tasamuh” (tolerant) are the core values of Islamic teaching. It has been known since the Prophet Muhammad SAW taught it. While the religious moderation within “Islam Nusantara” still not yet get wide attention, public assume that the religious moderation belongs to two large Islamic organization in Indonesia, Nahdlatul Ulama (NU) and Muhammadiyah. Both represents Indonesian version of moderate Islamic. In fact, the idea of “Islam Nusantara” has been long existing since the era of “Wali Songo” (the nine saints). Following up previously-mentioned ideas, this paper aims to address how religious moderation has been growing from the era the era of “Wali Songo” (the nine saints) to be “Islam Nusantara” (Islam of the Archipelago). These main aim also would to address the comparative analysis between“Wali Songo” (the nine saints) to be “Islam Nusantara” on current religious moderation.